The correct answer is:
(x + 3)^2 + (y + 2)^2 = 4^2, so the center is (–3, –2)
Further explanation:
The given equation of circle is:
![x^2+y^2+6x+4y-3 = 0](https://tex.z-dn.net/?f=x%5E2%2By%5E2%2B6x%2B4y-3%20%3D%200)
In order to complete the square the terms have to be combined first
![x^2+y^2+6x+4y = 3\\x^2+6x+y^2+4y=3\\(x^2+6x)+(y^2+4y) = 3](https://tex.z-dn.net/?f=x%5E2%2By%5E2%2B6x%2B4y%20%3D%203%5C%5Cx%5E2%2B6x%2By%5E2%2B4y%3D3%5C%5C%28x%5E2%2B6x%29%2B%28y%5E2%2B4y%29%20%3D%203)
9 and 4 will be added to both sides of the equation to complete the square
![(x^2+6x+9)+(y^2+4y+4) = 3+9+4\\(x^2+6x+9)+(y^2+4y+4) = 16](https://tex.z-dn.net/?f=%28x%5E2%2B6x%2B9%29%2B%28y%5E2%2B4y%2B4%29%20%3D%203%2B9%2B4%5C%5C%28x%5E2%2B6x%2B9%29%2B%28y%5E2%2B4y%2B4%29%20%3D%2016)
The next step completes the work
![(x+3)^2+(y+2)^2 = (4)^2\\](https://tex.z-dn.net/?f=%28x%2B3%29%5E2%2B%28y%2B2%29%5E2%20%3D%20%284%29%5E2%5C%5C)
Comparing with the standard form of circle
![(x-h)^2 + (y-k)^2 = r^2\\x - h = x+3\\h=-3\\y-k = y+2\\k = -2](https://tex.z-dn.net/?f=%28x-h%29%5E2%20%2B%20%28y-k%29%5E2%20%3D%20r%5E2%5C%5Cx%20-%20h%20%3D%20x%2B3%5C%5Ch%3D-3%5C%5Cy-k%20%3D%20y%2B2%5C%5Ck%20%3D%20-2)
As the centre is (h,k), the centre of given circle will be:
(-3,-2)
Hence the correct answer is:
(x + 3)^2 + (y + 2)^2 = 4^2, so the center is (–3, –2)
Keywords: Circle, Equation of Circle
Learn more about equations of circles at:
#LearnwithBrainly